2023
DOI: 10.1093/bjsopen/zrad129
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative uni- or multimodal prehabilitation on postoperative morbidity: meta-analysis

Amélie Cambriel,
Benjamin Choisy,
Julien Hedou
et al.

Abstract: Background Postoperative complications occur in up to 43% of patients after surgery, resulting in increased morbidity and economic burden. Prehabilitation has the potential to increase patients’ preoperative health status and thereby improve postoperative outcomes. However, reported results of prehabilitation are contradictory. The objective of this systematic review is to evaluate the effects of prehabilitation on postoperative outcomes (postoperative complications, hospital length of stay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 96 publications
0
0
0
Order By: Relevance
“…Despite previous studies in non-cardiac surgery, although in the presence of a heterogeneous offering of treatment/exercises and delivery methods, having demonstrated some benefits of a pre-admission period of rehabilitation-prehabilitation-in terms of reducing the length of stay in the ICU [36] and postoperative complications [37,38], there is no univocal evidence regarding its efficacy. Prior experiences with cardiac surgery patients showed that a prehabilitation program was also feasible for patients scheduled for CABG surgery [39] and was associated with reduced ICU and hospital lengths of stays, faster postoperative recovery and improved postoperative quality of life [40,41].…”
Section: Communication and Prehabilitationmentioning
confidence: 99%
“…Despite previous studies in non-cardiac surgery, although in the presence of a heterogeneous offering of treatment/exercises and delivery methods, having demonstrated some benefits of a pre-admission period of rehabilitation-prehabilitation-in terms of reducing the length of stay in the ICU [36] and postoperative complications [37,38], there is no univocal evidence regarding its efficacy. Prior experiences with cardiac surgery patients showed that a prehabilitation program was also feasible for patients scheduled for CABG surgery [39] and was associated with reduced ICU and hospital lengths of stays, faster postoperative recovery and improved postoperative quality of life [40,41].…”
Section: Communication and Prehabilitationmentioning
confidence: 99%